OPPORTUNITIES FOR THE DEVELOPMENT OF AGROTURISM ON THE BASIS OF ATTRACTING FOREIGN INVESTMENT (Academicia Globe: Inderscience Research, 2021)
The article describes in detail the opportunities and stages of development of agritourism in Uzbekistan and its components. The analysis is based on the possibility of introducing an agricultural and tourism cluster. At the same time, proposals and recommendations have been developed on the need to attract investment in the development of agritourism and the priorities for its further improvement.